2018
DOI: 10.1080/15384101.2018.1482150
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α induces autophagy through ERK1/2 pathway to regulate apoptosis in neonatal necrotizing enterocolitis model cells IEC-6

Abstract: Necrotizing enterocolitis (NEC) is a potentially fatal illness in premature neonates. Tumor necrosis factor-α (TNF-α) and autophagy are associated with the pathogenesis of NEC. This study aimed to explore whether TNF-α might regulate apoptosis in neonatal NEC model cells IEC-6 via regulation of autophagy. NEC rat model was induced by hand feeding and exposure to asphyxia/cold-stress for histologic examination. The NEC in vitro model (IEC-6/NEC cells) was established by stimulating the intestinal epithelial cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 40 publications
3
49
0
Order By: Relevance
“…As autophagic and apoptotic programs appear to inhibit each other (42), and apoptosis participates in the DC life cycle and elimination after maturation (8), we investigated if Dab2 deletion could impact DC apoptosis. To test that, DC2.4 WT and DC2.4 Dab2 − / − DCs were treated with staurosporine, an apoptosis inducer, for up to 3 h and apoptosis was detected by 7AAD/Annexin V labeling and flow cytometry and by Western blot analysis of the cleaved caspase-3 (17 kDa) expression.…”
Section: Resultsmentioning
confidence: 99%
“…As autophagic and apoptotic programs appear to inhibit each other (42), and apoptosis participates in the DC life cycle and elimination after maturation (8), we investigated if Dab2 deletion could impact DC apoptosis. To test that, DC2.4 WT and DC2.4 Dab2 − / − DCs were treated with staurosporine, an apoptosis inducer, for up to 3 h and apoptosis was detected by 7AAD/Annexin V labeling and flow cytometry and by Western blot analysis of the cleaved caspase-3 (17 kDa) expression.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we showed that TNF‐α‐induced autophagy also contributes to a decrease in BMPR2 levels. One of the presumed mechanisms on how inflammation induces autophagy might be through ERK1/2 MAP kinase pathway activation . In addition, TNF‐α has also been shown to upregulate the expression of the autophagy genes LC3 and beclin 1 through Jun kinase signalling pathway activation and AKT/PKB inhibition .…”
Section: Discussionmentioning
confidence: 99%
“…Intraperitoneal injection of chloroquine, an autophagy inhibitor, attenuates excessive inflammatory response in DSS-treated erbin -/mice [18]. Using in vitro and in vivo models of neonatal necrotizing enterocolitis, an inflammatory intestinal disease of new-born infants, it was reported that TNF induces autophagy via the MAPK1/ERK2 (mitogen-activated protein kinase 1)-MAPK3/ERK1 pathway to suppress cell proliferation and promote apoptosis, which might consequently favor disease development [19]. Even if these studies diverged in the precise mechanism of cell death, they all suggested that defective autophagy may lead to an excessive level of epithelial cell death, favoring IBD development.…”
Section: Autophagy and Epithelial Cell Deathmentioning
confidence: 99%